Produção de biocombustíveis em diferentes escalas via craqueamento térmico catalítico de resíduos de caixa de gordura com catalisador Na2CO3 - CORRÊA, Onésimo Amorim (Universidade Federal do Pará, 2017)
This paper presents the residual fat taken from retaining grease traps as a potential feedstock for the production of alternative and renewable fuels. The residual oil was used as filler in experiments catalytic thermal cracking countertop units, Semi-pilot and pilot. Different levels of sodium carbonate (5%, 10% and 15%) were used as a catalyst in the catalytic thermal craqueamneto experiments. Organic liquids (PLO's) obtained in the cracking experiments were distilled in distillation units in bench and pilot scale. Distillation processes resulted in the development of hydrocarbon fractions in kerosene bands, light and heavy diesel. The PLO's with the green light and heavy diesel fractions were characterized according to the specifications established by the standard of ANP 65 for diesel S10. The green kerosene fractions were characterized according to the specifications established by the standard of ANP 37 for petroleum-based kerosene. The results showed that the PLO's had low values for the acid value, moreover, it was confirmed that the use of different percentages of catalyst ash in the three scales of production contributed to obtaining promising results in terms of yield and physico -chemical and compositional, indicating the efficiency of this basic catalyst. The results also showed that the fractions of green kerosene, heavy and light green diesel had low levels of free fatty acids, significant income and physical and chemical characteristics in line with their respective standards. The experiments using the percentage of 10% sodium carbonate as catalyst showed the highest incomes, lower levels of acidity and the best results of physicochemical and compositional characterization of all the tests in this study. The PLO produced using the level of 10% of sodium carbonate showed a total of 78.98% of hydrocarbons in the composition, while the green kerosene obtained after distillation of the same PLO showed 92.64% total hydrocarbons in its composition, these results were confirmed by analysis as FT-IR, RMN and GC-MS.